Gathering requirements for IoT-assisted wellbeing in elementary school—a multi-stakeholder perspective - Brodén, Karin; Andersson, Jonas; Kitkowska, Agnieszka; Ahmad, Awais; Mozelius, Peter (Frontiers in Education, 2025)
IntroductionStudents experiencing poor wellbeing in elementary school can suffer lifelong consequences, including low self-esteem or depression. Understanding how to increase student wellbeing through information-based approaches is therefore important. While previous research has explored wellbeing frameworks, this study uniquely investigates the intersection of elementary school wellbeing with Internet of Things (IoT) implementation potential.MethodWe present the first comprehensive requirements analysis gathered from both staff and students for improving wellbeing in an elementary school in rural Sweden, with the aim of implementing IoT solutions. We collected qualitative data through individual interviews and workshops with 25 staff members and a survey from 464 students. We analyzed the data in an inductively and deductively way, using the Konu and Rimpelä’s wellbeing framework.ResultsOur novel findings reveal alignment between staff and student perspectives across the framework’s categories: having, loving, being and health. One example is the importance of motivation in each learning situation and creating a foundation for good social relations among the students. The requirements related to the health category received the least attention, reflecting less focus on individual student circumstances.DiscussionThis study contributes new knowledge by detailing wellbeing needs for elementary school and relating them to data-driven innovation, such as IoT, for gathering both objective and subjective information. We also acknowledge that this creates additional demands on current solutions and raises significant privacy concerns in school environments. Future research will incorporate expert IoT knowledge and develop prototype solution based on these identified requirements.